Pentingnya Penggunaan Bahasa Inggris dalam Komunikasi Dakwah pada Era Global - Juriana Juriana (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2017)
English is a global language that very important in multidiscipline aspects since it was decided to be international language, include used in da’wah communication. Da’wah communication is communication that done between communicator (da’i) dan communicant (mad’u) to give information and massege having sources of Al-Quran and hadith in other to being called of communicant’s heart to Islamic religion to learn, think, and do in daily activities of life. The important of using English in da’wah communication on the global era are: 1) English can make da’wah communication be easy to give the message to the native speaker audience (mad’u), 2) English as mediator language in solving problem like inter-religious conflict, 3) English can be the foundation for a country to compete other countries, and 4) English as important role holder to spread of understanding about Islam religion.